2008
DOI: 10.1007/s11631-008-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and geological significance of carbazole compounds in Silurian paleo-pools of the Tarim Basin, Northwest China

Abstract: The results presented in this paper indicated that the carbazole-type compounds have high thermal stability and also show stability in oxidation and bio-degradation. This kind of compounds still has high concentrations and a complete distribution in the analyzed dry asphalt samples, showing that they are particularly useful in the study of hydrocarbon migration of the paleo-pools. The difference in the contents of nitrogen compounds in the Silurian dry asphalts from the Awati, Tabei and Tazhong areas is attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…So DDTs in rice mainly come from growing environment, residual DDT characteristics of rice can represent its DDT existing condition. The studies show that (DDD+DDE)/DDT is regarded as standard whether there are new DDT input, if (DDD+DDE)/DDT > 1, the DDT degrade completely almost and no new pollution input; if (DDD+DDE)/DDT< 1, shows that there is new DDT pollution input [7,14]. The results shown in Fig.…”
Section: The Analysis Of Ddt's Sources In Early Rice and Late Ricementioning
confidence: 95%
See 1 more Smart Citation
“…So DDTs in rice mainly come from growing environment, residual DDT characteristics of rice can represent its DDT existing condition. The studies show that (DDD+DDE)/DDT is regarded as standard whether there are new DDT input, if (DDD+DDE)/DDT > 1, the DDT degrade completely almost and no new pollution input; if (DDD+DDE)/DDT< 1, shows that there is new DDT pollution input [7,14]. The results shown in Fig.…”
Section: The Analysis Of Ddt's Sources In Early Rice and Late Ricementioning
confidence: 95%
“…Organochlorine pesticide once was used in large qualities in China, the usage of organochlorine pesticide per acre was 250g, it is about 60g per acre higher than US, harvest was brought to us, as well as potential dangers [5,6]. Although the production and usage of organochlorine pesticides such as DDT, BHC are forbidden, further study found that the residual DDTs in various soils, biological bodies and agricultural productions, it also is found in human milk [7], even it is traced in the polar biological bodies [8], the researches show that the current status of residual DDTs is not optimistic.…”
Section: Introductionmentioning
confidence: 99%